Contributions of non-timber forest products to household food security and income around Onigambari forest reserve, Oyo State, Nigeria (2007)
"The study evaluated the contributions of non-timber forest products (NTFPs) to household income and food security in the adjoining villages of Gambari forest reserve Nigeria. Stratified random sampling was used to select respondents among the community members. 141 copies of questionnaires were administered among consumers and marketers of NTFPs. The data obtained were subjected to descriptive statistics, t-test and rate of return on investment (RORI). Results indicate that 61.7% of the marketers were involved in NTFPs marketing on full time basis and 63.12% of them were females. Ten important NTFPs were found to contribute to food in -take and income in the area. Sixty one percent of the respondents obtained the products from the forest. Vegetables are consumed with 45.4% of their meals on a year round basis. The contributions of NTFPs to household income amount to 68.1% of total monthly income. The difference in monthly income generated from NTFPs and other sources is significant (p < 0.05). Fuel wood is used by 46.09 % of the respondents as a source of energy for cooking and preserving foods. It is recommended that important NTFPs be integrated into the traditional farming system so as to enhance sustainable supplies. The NTFPs should also be developed in terms of value addition in order to promote efficient resource utilization. Also, proper inventory of the forest should be carried out to assess the stocking level and determine potential yield to guard against over-exploitation. "